2014
DOI: 10.1186/1472-6831-14-48
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light-curing mode on the cytotoxicity of resin-based surface sealants

Abstract: Background: Surface sealants have been successfully used in the prevention of erosive tooth wear. However, when multiple tooth surfaces should be sealed, the light-curing procedure is very time-consuming. Therefore, the aim of this study was to investigate whether reduced light-curing time (while maintaining similar energy density) has an influence on resin-based surface sealant cytotoxicity. Methods: Bovine dentine discs were treated as follows: group 1: untreated, groups 2-5: Seal&Protect and groups 6-9: exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…The degree of conversion is an essential material characteristic of dental resin composites, affecting both physical and mechanical as well as biological polymer properties [34][35][36][37][38][39][40][41]. In the current study, the added micro-fillers did not affect the degree of conversion at the specimens' top surface, irrespective of the bulk-fill composite used.…”
Section: Discussionmentioning
confidence: 48%
“…The degree of conversion is an essential material characteristic of dental resin composites, affecting both physical and mechanical as well as biological polymer properties [34][35][36][37][38][39][40][41]. In the current study, the added micro-fillers did not affect the degree of conversion at the specimens' top surface, irrespective of the bulk-fill composite used.…”
Section: Discussionmentioning
confidence: 48%
“…Degree of conversion (DC) was measured using a Fourier transform infrared spectrometer (Cary 630 FTIR; Agilent Technologies, Santa Clara, CA, USA) with an attenuated total reflectance (ATR) accessory [41]. The same amount of composite (42 mm 3 ) as for assessment of linear shrinkage and shrinkage force was applied on the ATR diamond crystal with the aid of a 1.5 mm thick cylindrical Teflon mold, which was covered with a sandblasted (aluminum oxide, 50 μm; Renfert) and silanized (Monobond Plus; Ivoclar Vivadent) glass plate.…”
Section: Degree Of Conversionmentioning
confidence: 99%
“…The degree of conversion (DC) represents a fundamental parameter governing mechanical properties and biocompatibility of polymer-based materials [18][19][20][21]. Previous studies indicated that BG 45S5 can impair the DC of experimental resin composites [22][23][24].…”
Section: Introductionmentioning
confidence: 99%